123I-BMIPP/201Tl dual myocardial SPECT proves the efficacy of surgical treatment for an adult with Bland–White–Garland syndrome. Issue 1 (January 2020) - Yuzawa-Tsukada, Naoko; Kashiwagi, Yusuke; Fukushima, Keisuke; Shirasaki, Keisuke; Oki, Yoshitsugu; Kamba, Takahito; Kubota, Takeyuki; Miyanaga, Satoru; Muramatsu, Koichi; Kawada, Noriyasu; Naganuma, Hirokuni; Komukai, Kimiaki; et al.
Abstract: Bland–White–Garland (BWG) syndrome is a rare congenital heart disease in which the left coronary artery originates from the pulmonary artery (PA). Surgical treatment to rebuild a dual coronary system is recommended at the time of the diagnosis. However, no effective operative procedure has been established for adult-type BWG patients because of the paucity of such cases. We herein report a case of adult-type BWG that was successfully treated by patch closure of the orifice of the left main tract from the main PA and coronary artery bypass grafting. 123 I-15-(p-iodophenyl)-3-(R, S)-methylpentadecanoic acid (BMIPP) and 201 thallium (Tl) dual myocardial single-photon emission computed tomography (SPECT) were performed before surgery, early after surgery, and at three months after surgery. Before surgery, dual SPECT showed myocardial perfusion defects in the anterior and septal wall, which corresponded to the cardiovascular magnetic resonance imaging findings. Early after surgery, only 201 Tl images demonstrated an improvement in the defect area. At three months after surgery, both the 201 Tl and 123 I-BMIPP imaging findings demonstrated an improvement in the defect area, which was correlated with the recovery of the left ventricular function. These results showed the effectiveness of this surgical approach for BWG syndrome. <Learning objective: Adult-type Bland–White–Garland syndrome is a rare congenital disease and no effective operative procedure has been established because of the paucity of such cases. The patient in this report underwent patch closure of the orifice of the left main tract from the main pulmonary artery and coronary artery bypass grafting. Myocardial dual single-photon emission computed tomography was considered to be effective for evaluating the results of revascularization surgery, and an improved uptake on 123 I-15-(p-iodophenyl)-3-(R, S)-methylpentadecanoic acid images was closely related to an improvement in the left ventricular function.>